The Role of Academic Libraries in Contributing to Students Academic Achievement - Luqman Ayanlola Atanda (MANDALIKA : Journal of Social Science, 2026)
Academic libraries play a crucial and evolving role in promoting student success within higher education. Beyond providing access to diverse collections of print and digital materials, libraries actively contribute to academic achievement through tailored support services, research assistance, and information literacy training. This research is a Descriptive analytical researchs with a focus on case studies in the field of higher education. The purpose of this study is to confirm that academic libraries are a crucial element in creating an effective, equitable, and dynamic learning environment that contributes directly to student success. This work examines how libraries adapt to the changing educational landscape by fostering inclusive learning environments, partnering with campus agencies, and addressing the needs of underrepresented groups. It highlights the positive correlation between library engagement and academic performance, particularly among first-generation and distance-learning students. Challenges such as limited resources and fragmented feedback systems are also discussed, with recommendations for leveraging data-driven approaches to enhance library services and better support diverse student populations. Ultimately, the work underscores the integral role of academic libraries in shaping equitable, dynamic, and effective learning environments that drive student success